2019
DOI: 10.2147/ijn.s218760
|View full text |Cite
|
Sign up to set email alerts
|

<p>EDTA-modified mesoporous silica as supra adsorbent of copper ions with novel approach as an antidote agent in copper toxicity</p>

Abstract: PurposeMesoporous silica (MS) have been considered as a biocompatible compound and found to have various pharmaceutical applications. Recently, novel approaches in applications of MS as antidote agents were introduced. In this study, the capacity of ethylenediaminetetraacetic acid modified mesoporous silica (MS-EDTA) was evaluated in in vitro and in vivo adsorption of copper (Cu).MethodsThe MS-EDTA was characterized by fourier transform infrared (FT-IR) and X-ray diffraction, while surface area was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The MS-NH 2 preparation method is summarized here. 19 Firstly, 4.8 g of CTAB (13.2 mmol) as a surfactant template was dissolved in 100 mL of deionized water. In the next step, 26 mL of ammonia was added to the above solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MS-NH 2 preparation method is summarized here. 19 Firstly, 4.8 g of CTAB (13.2 mmol) as a surfactant template was dissolved in 100 mL of deionized water. In the next step, 26 mL of ammonia was added to the above solution.…”
Section: Methodsmentioning
confidence: 99%
“… 13 In this regard, Farjadian et al reported that EDTA modified MS could be potent antidote agents while assessed in vitro and in vivo in adsorption of iron 18 and copper. 19 …”
Section: Introductionmentioning
confidence: 99%
“…In continuous of our previous studies in the field of toxicology by introducing novel antidote agents made of mesoporous silica with high capacity in adsorption of paracetamol and phenobarbital [ 18 ], iron [ 19 ], and copper [ 20 ], and management of hepatic encephalopathy [ 17 ], herein, SVLM is repurposed as a distinguishing antidote of AlP.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it would be easy for the modification of the functional group on MSNs’ surface to achieve the long period release of therapeutic agents. 2 , 3 For example, Shah’s group 4 fabricated a Velpatasvir (VLP) loaded MSNs with good biocompatibility, and this MSNs based drug delivery system showed prolonged VLP release both in vitro and in vivo. Meantime, a study by Yang et al 5 revealed a preparation of Breviscapine (BRE) loaded MSNs, which showed higher dissolution rate and higher oral absorption than BRE powder.…”
Section: Introductionmentioning
confidence: 99%